1986
DOI: 10.1109/tpwrd.1986.4308057
|View full text |Cite
|
Sign up to set email alerts
|

Natural Aging of Non-Energized Aluminum Conductors

Abstract: This paper reports the results of a photographic and electrical study of the mechanism by which a new aluminum conductor ages. A systematic approach of monitoring the aging process revealed thermDvement of water drop location from the top of a new conductor to the bottom of an aged conductor. Through photographic water drop analysis and electrical test results it has been determined that an aluminum conductor, even though not energized, is essentially aged in 4 to 7 months in the environment of northern Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Wetting can vary widely for different conductors. In particular, ageing of the conductor cables results in a considerable change in hydrophilicity of the cable surfaces [11] drops, while on the sides of the cables bigger drops are situated, while on well aged conductors only large drops on the under side of the conductors are present.…”
Section: Double Bundlementioning
confidence: 99%
See 2 more Smart Citations
“…Wetting can vary widely for different conductors. In particular, ageing of the conductor cables results in a considerable change in hydrophilicity of the cable surfaces [11] drops, while on the sides of the cables bigger drops are situated, while on well aged conductors only large drops on the under side of the conductors are present.…”
Section: Double Bundlementioning
confidence: 99%
“…To solve the system of equations at a time t l , b k (t l ) has to be determined first. For this purpose the electric field on the surface E k is taken according to E k = E k (q i (t l ), q ds (t l+1 )) for comparison with E ck according to (11).…”
Section: The Injection Of Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface roughness factor was employed to evaluate the degree of roughness of the electrodes by Peek in 1929 [4], and it is reported in [5] that is in the range of 0.82 to 0.92 for new conductors while 0.4 to 0.8 is for aged conductors. Booker characterized the surface morphologies of several natural aging conductors by a camera [6]. Suda [7] and Ma [8] described the surface conditions of "artificially polluted" conductors by means of cameras equivalent salt deposit density of the contaminations on their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…After the atmospheric aging period for 4 months, it was observed that the corona onset voltages of the conductors raised to a certain extent, at the same time, the audible noise level in 8 kHz expressed a decrease tendency. Unfortunately Booker did not keen on the investigation after the initial aging period [25].…”
Section: Introductionmentioning
confidence: 99%